Biomass resin composition and molded article

JP2026165261APending Publication Date: 2026-10-14KITAGAWA INDS
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025057553
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

Smart Images

  • Figure 2026165261000001
    Figure 2026165261000001
  • Figure 2026165261000002
    Figure 2026165261000002
Patent Text Reader

Abstract

The present invention provides a biomass resin composition that exhibits excellent flame retardancy and mechanical strength despite the addition of biomass materials, and a molded article thereof. [Solution] The biomass resin composition is a mixture of polycarbonate, a biomass material mainly composed of calcium carbonate, a hydrogenated styrene thermoplastic elastomer, a dispersant made of an acid-modified resin, and either a brominated flame retardant or a phosphazene flame retardant. When the biomass resin composition is 100 parts by mass, it contains 13 to 48 parts by mass of polycarbonate, 10 to 45 parts by mass of biomass material, and 0.75 to 1.5 parts by mass of dispersant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a biomass resin composition and a molded article.

Background Art

[0002] Patent Document 1 below discloses a thermoplastic resin composition, and discloses an example in which an inorganic filler is blended as one component thereof. Calcium carbonate is disclosed as an example of the inorganic filler.

Prior Art Literature

Patent Documents

[0003]

Patent Document 1

Summary of Invention

Problem to be Solved by the Invention

[0004] In the course of efforts toward carbon neutrality, the present inventors have studied blending a biomass material containing calcium carbonate as a main component into a resin composition. However, when the blending amount of the biomass material is increased, there is a problem that the mechanical strength of the molded article decreases.

[0005] Against such a background, the present inventors have repeatedly studied the types, blending ratios and the like of components blended into the resin composition. As a result, the present inventors have found a material configuration and a blending ratio that allow desired flame retardancy and mechanical strength to be exhibited even when a certain amount of the biomass material is blended, and have completed the technique of the present disclosure.

[0006] In one aspect of the present disclosure, it is desirable to provide a biomass resin composition that exhibits excellent flame retardancy and mechanical strength despite being blended with a biomass material, and a molded article thereof.

Means for Solving the Problem

[0007] (1) One aspect of the present disclosure is a biomass resin composition comprising polycarbonate, a biomass material mainly composed of calcium carbonate, a hydrogenated styrene thermoplastic elastomer, a dispersant consisting of an acid-modified resin, and one of a brominated flame retardant or a phosphazene flame retardant. When the total biomass resin composition is 100 parts by mass, it comprises 13 to 48 parts by mass of polycarbonate, 10 to 45 parts by mass of biomass material, and 0.75 to 1.5 parts by mass of dispersant.

[0008] The biomass resin composition configured in this manner exhibits excellent mechanical strength after molding and sufficient flame retardancy, despite containing biomass material. The effects of the biomass resin composition of this disclosure will become clearer in more detail in the embodiments described later.

[0009] Furthermore, the technology disclosed herein may also include the following configurations. (2) In one embodiment of the present disclosure, a brominated flame retardant may be added in an amount of 32 to 38 parts by mass, and a hydrogenated styrene thermoplastic elastomer may be added in an amount of 6 to 10 parts by mass.

[0010] (3) In one embodiment of the present disclosure, a phosphazene-based flame retardant may be added in an amount of 7 to 15 parts by mass, and a hydrogenated styrene-based thermoplastic elastomer may be added in an amount of 5 to 13 parts by mass. Furthermore, this disclosure may have the following configuration:

[0011] (4) One aspect of the present disclosure is a molded article obtained by molding the biomass resin composition described above. [Modes for carrying out the invention]

[0012] Next, the biomass resin composition described above will be explained with reference to exemplary embodiments. [Composition of biomass resin composition] In the biomass resin composition of this disclosure, 13 to 48 parts by mass of polycarbonate are blended in 100 parts by mass of the biomass resin composition.

[0013] Furthermore, the biomass resin composition of this disclosure contains a biomass material mainly composed of calcium carbonate. An example of a biomass material mainly composed of calcium carbonate is a biomass filler made by crushing and pulverizing seashells to a degree that allows them to be filled into the resin material. Examples of seashells include scallop shells and oyster shells. The biomass material may also be made from materials other than seashells. For example, eggshells may be used as a raw material.

[0014] One way for companies to clearly indicate to consumers that their products are biomass-derived is to affix the "Biomass Mark," certified by the Japan Organic Resources Association, to their products. To obtain Biomass Mark certification, a product must consist of at least 10% biomass material.

[0015] Therefore, when considering the total amount of biomass material, it is preferable to include 10 parts by mass or more of biomass material when the total biomass resin composition is 100 parts by mass. On the other hand, from the viewpoint of ensuring sufficient mechanical strength of the molded product, it is preferable to include 45 parts by mass or less of biomass material. The more biomass material is included, the more effective it is in terms of carbon neutrality efforts, so 10 to 45 parts by mass is preferable, 31 to 45 parts by mass is more preferable, and 41 to 45 parts by mass is even more preferable.

[0016] On the other hand, incorporating a large amount of biomass material mainly composed of calcium carbonate leads to a problem of reduced mechanical strength after molding. To solve this problem, the biomass resin composition of this disclosure contains 5 to 13 parts by mass of hydrogenated styrene-based thermoplastic elastomer per 100 parts by mass of the biomass resin composition.

[0017] When using a brominated flame retardant, if the amount of hydrogenated styrene-based thermoplastic elastomer is 6 parts by mass or more, good results tend to be obtained in the evaluation of impact strength after molding. When using a brominated flame retardant, if the amount of hydrogenated styrene-based thermoplastic elastomer is 10 parts by mass or less, flexibility after molding can be ensured, and good results tend to be obtained in the bending strength test.

[0018] When using phosphazene-based flame retardants, a blending amount of hydrogenated styrene-based thermoplastic elastomer of 5 parts by mass or more tends to yield good results in the evaluation of impact strength after molding. A blending amount of hydrogenated styrene-based thermoplastic elastomer of 13 parts by mass or less tends to ensure flexibility after molding and yield good results in the bending strength test.

[0019] The amount of dispersant added is preferably 0.75 to 1.5 parts by mass per 100 parts by mass of the biomass resin composition. When the amount of dispersant is 0.75 parts by mass or more, the filler is sufficiently mixed, and the measurement results of MFR (Melt Flow Rate), one of the indicators of the fluidity of thermoplastic resins, tend to be good. On the other hand, when the amount of dispersant is 1.5 parts by mass or less, good results regarding flame retardancy tend to be obtained.

[0020] When a brominated flame retardant is incorporated as a flame retardant, it is preferable to incorporate 32 to 38 parts by mass of the brominated flame retardant per 100 parts by mass of the biomass resin composition. By incorporating 32 parts by mass or more of the brominated flame retardant, the desired flame retardancy can be ensured. Since flame retardancy improves with a higher amount of flame retardant, it is more preferable to incorporate 34 parts by mass or more of the brominated flame retardant.

[0021] When a phosphazene-based flame retardant is used as a flame retardant, it is preferable to include 7 parts by mass or more of the phosphazene-based flame retardant per 100 parts by mass of the biomass resin composition, and more preferably 7 to 15 parts by mass.

[0022] Furthermore, focusing on the evaluation of flame retardancy, the intended flame retardancy can be achieved when all of calcium carbonate, hydrogenated styrenic thermoplastic elastomer, and dispersant are adjusted to be not more than the upper limit values of the numerical ranges specified in the present disclosure.

[0023] Focusing on the evaluation of the screw tightening torque test, favorable results can be obtained in the screw tightening torque test when all of polycarbonate and hydrogenated styrenic thermoplastic elastomer are adjusted to be not less than the lower limit values of the numerical ranges specified in the present disclosure.

[0024] The matters described above will be apparent from the Examples and Comparative Examples described later. [Production Examples of Biomass Resin Composition] The respective materials shown in the following Table 1 and Table 2 were mixed at the mass ratios shown in the following Table 1 and Table 2 to produce biomass resin compositions. In addition, Examples 1 to 12 described in the following Table 1 are biomass resin compositions that satisfy the compounding ratios specified in the present disclosure. Comparative Examples 1 to 7 described in Table 2 are biomass resin compositions that do not satisfy the compounding ratios specified in the present disclosure.

[0025] Among the respective materials shown in the following Table 1 and Table 2, as the base material, polycarbonate manufactured by Teijin Limited (trade name: Panlite (registered trademark) L-1225L) was used. As the biomass material, scallop biomass filler (main component: calcium carbonate, particle size: 4 μm) manufactured by Tomoe Engineering Co., Ltd. was used.

[0026] Examples of hydrogenated styrene-based thermoplastic elastomers include, for example, hydrogenated styrene-butadiene copolymers. In this embodiment, a hydrogenated styrene-based thermoplastic elastomer manufactured by Asahi Kasei Corporation (product name: ToughTec® M1943) was used as the hydrogenated styrene-based thermoplastic elastomer. Examples of dispersants made of acid-modified resins include, for example, malean anhydride of olefin resins. In this embodiment, a dispersant manufactured by Sanyo Chemical Industries, Ltd. (product name: Yumex® 1001) was used as the dispersant. Two types of flame retardants were used as flame retardants. The first flame retardant was a bromine-based flame retardant manufactured by Suzuhiro Chemical Co., Ltd. (product name: Hiromaster F-101). The second flame retardant was a phosphazene-based flame retardant manufactured by Mitsui Chemicals Fine, Inc. (product name: Rabitol® FP-110).

[0027] These materials were kneaded for 5 minutes at 20 rpm and 220°C using a commercially available kneading and extrusion testing device (product name: Laboplastmill®, manufactured by Toyo Seiki Seisakusho Co., Ltd., model 4C150). The kneaded biomass resin composition was then molded into a sheet using a press at 220°C, 5 MPa, and for 1 minute.

[0028] Next, the samples from Examples 1 to 12 and Comparative Examples 1 to 7 were evaluated for flame retardancy, mechanical strength (bending strength, impact strength, screw tightening torque test), and MFR (Melt Flow Rate). Of these evaluation items, flame retardancy was evaluated using 2 mm thick test pieces in accordance with UL94, and the evaluation results were assessed in four stages: V-0, V-1, V-2, and no flame retardancy. Samples with results of V-0, V-1, or V-2 were considered acceptable. For bending strength, the bending strength was measured in accordance with JIS K7171, and a measured value of 45 MPa or higher was considered acceptable.

[0029] Regarding impact strength, the Charpy impact strength without notches was measured in accordance with JIS K 7111, and the measured value was 17 kJ / m 2The sample was deemed to pass if it met the above criteria. For the screw tightening torque test, the resin plate thickness was 6 mm, the screw hole diameter was 3 mm, the screw hole processing area was 2 mm from the edge of the resin plate, two types of screws were used (non-sert screws and P-tight screws), and the torque was set to 1.7 N·m. The sample was deemed to pass if no cracks occurred in the screw hole as a result of the measurement. For MFR, the measurement was performed using a melt indexer F-F01 manufactured by Toyo Seiki Seisakusho at a temperature of 230°C and a load of 10 kg, and a value of 5 g / 10 min or higher was deemed to pass. The overall judgment was that the sample passed if all of these evaluations were met. The test results for each sample are also listed in Tables 1 and 2 below.

[0030] [Table 1]

[0031] [Table 2]

[0032] As shown in Table 1 above, the flame retardancy evaluation results for the samples in Examples 1 to 12 were either V-0, V-1, or V-2. The flexural strength of the samples in Examples 1 to 12 were all 45 MPa or higher, and the impact strength of all was 17 kJ / m 2 The above conclusions were reached. Furthermore, in the screw tightening torque test, no cracks occurred in the screw holes of any of the samples from Examples 1 to 12. In addition, the MFR of all samples from Examples 1 to 12 was 5g / 10min or higher. Based on these results, the samples from Examples 1 to 12 passed the overall evaluation.

[0033] On the other hand, as shown in Table 2 above, the samples of Comparative Examples 1 to 7 failed to meet the acceptance criteria in at least one of the following items: flame retardancy, bending strength, impact strength, screw tightening torque test, and MFR. Therefore, the samples of Comparative Examples 1 to 7 failed the overall assessment.

[0034] More specifically, in Comparative Example 1, compared to Example 3, the amount of biomass material was increased by 1 part by mass, while the amount of polycarbonate was decreased by 1 part by mass. As a result, Comparative Example 1 failed all evaluations, including flame retardancy, screw tightening torque test, and MFR, and the overall judgment was a failure. Thus, it was found that even a slight difference in the amount of biomass material can result in completely different physical properties of the biomass resin composition, and that it is important to limit the amount of biomass material in a biomass resin composition to 45 parts by mass or less per 100 parts by mass.

[0035] In Comparative Example 2, the amount of hydrogenated styrene-based thermoplastic elastomer was reduced by 1 part by mass compared to Example 4, while the amount of polycarbonate was increased by 1 part by mass. As a result, the impact strength and screw tightening torque tests failed, and the overall evaluation was also a failure. Furthermore, in Comparative Example 3, the amount of hydrogenated styrene-based thermoplastic elastomer was increased by 1 part by mass compared to Example 5, while the amount of polycarbonate was reduced by 1 part by mass. As a result, the flame retardancy and flexural strength tests failed, and the overall evaluation was also a failure.

[0036] These results indicate that when using brominated flame retardants, it is important that the amount of hydrogenated styrene-based thermoplastic elastomer in 100 parts by mass of the biomass resin composition is between 6 and 10 parts by mass. In particular, in the evaluation of flexural strength, it was found that even a difference of just 1 part by mass in the amount of hydrogenated styrene-based thermoplastic elastomer from the upper and lower limits of the blending range found in this disclosure resulted in a difference of approximately 9 MPa to 11 MPa in flexural strength. This shows that when using brominated flame retardants, even slight differences in the amount of hydrogenated styrene-based thermoplastic elastomer have a significant impact on the flexural strength after molding.

[0037] In Comparative Example 4, the amount of dispersant was reduced by 0.25 parts by mass compared to Example 6, while the amount of polycarbonate was increased by 0.25 parts by mass. As a result, the MFR evaluation failed, and the overall judgment was also a failure. Furthermore, in Comparative Example 5, the amount of dispersant was increased by 0.5 parts by mass compared to Example 7, while the amount of polycarbonate was reduced by 0.5 parts by mass. As a result, the flame retardancy evaluation failed, and the overall judgment was also a failure.

[0038] In particular, in Comparative Example 5, simply by adding 0.5 parts by mass more dispersant than in Example 7, the flame retardancy rating dropped from the highest rating of "V-0" to "No flame retardancy." From these results, it was found that the amount of dispersant added, between 0.75 parts by mass and 1.5 parts by mass, not only affects the MFR value after molding but also significantly contributes to not impairing flame retardancy.

[0039] In Comparative Example 6, the amount of brominated flame retardant was reduced by 1 part by mass compared to Example 8, while the amount of polycarbonate was increased by 1 part by mass. As a result, the flame retardancy evaluation failed, and the overall judgment was also a failure. Furthermore, in Comparative Example 7, the amount of brominated flame retardant was increased by 1 part by mass compared to Example 10, while the amount of polycarbonate was reduced by 1 part by mass. As a result, the screw tightening torque test evaluation failed, and the overall judgment was also a failure.

[0040] In examining the evaluation results of this screw tightening torque test, in addition to Example 10 and Comparative Example 7, Comparative Examples 1 and 2, which failed the screw tightening torque test, can be referred to. As mentioned above, polycarbonate and hydrogenated styrene-based thermoplastic elastomers are blended to increase mechanical strength.

[0041] However, when a brominated flame retardant is included, if the amount of polycarbonate in 100 parts by mass of the biomass resin composition is less than 13 parts by mass, a satisfactory evaluation in the screw tightening torque test cannot be obtained. Also, when a brominated flame retardant is included, if the amount of hydrogenated styrene-based thermoplastic elastomer in 100 parts by mass of the biomass resin composition is less than 6 parts by mass, a satisfactory evaluation in the screw tightening torque test cannot be obtained.

[0042] In Examples 11 and 12, a phosphazene-based flame retardant was used instead of the brominated flame retardant used in Examples 8 to 10. Regarding the amount of phosphazene-based flame retardant, it is preferable to include 7 parts by mass or more of the phosphazene-based flame retardant per 100 parts by mass of the biomass resin composition, and more preferably 7 to 15 parts by mass.

[0043] A higher MFR value indicates better fluidity and easier molding; therefore, from an MFR perspective, phosphazene-based flame retardants are considered easier to use in manufacturing molded products than brominated flame retardants. Conversely, poor MFR measurement results are undesirable because they can lead to quality defects when molding biomass resin compositions for industrial use.

[0044] As these results show, the technology of this disclosure allows for the production of a biomass resin composition that, despite containing a biomass material at a level that allows for the application of the biomass mark, exhibits excellent mechanical strength after molding, superior flame retardancy, and a superior MFR value. In order to obtain such a biomass resin composition and molded articles that are superior from the standpoint of manufacturing and quality for industrial applications, it is important to use the optimal material composition and blending ratio discovered by the inventors in this disclosure.

[0045] [Other embodiments] Although the biomass resin composition has been described above with reference to exemplary embodiments, the embodiments described above are merely illustrative examples of one aspect of the disclosure. In other words, the disclosure is not limited to the exemplary embodiments described above, and can be implemented in various forms without departing from the technical spirit of the disclosure.

[0046] For example, multiple functions realized by one component as illustrated in the above embodiment may be realized by multiple components. One function realized by one component as illustrated in the above embodiment may be realized by multiple components. Multiple functions realized by multiple components as illustrated in the above embodiment may be realized by one component. One function realized by multiple components as illustrated in the above embodiment may be realized by one component. Some of the configurations illustrated in the above embodiment may be omitted.

[0047] [Technical concepts disclosed in this specification] [Item 1] A biomass resin composition, A dispersant consisting of polycarbonate, a biomass material mainly composed of calcium carbonate, a hydrogenated styrene-based thermoplastic elastomer, and an acid-modified resin, and one of either a brominated flame retardant or a phosphazene-based flame retardant, However, it is included in the formula. When the entire biomass resin composition is 100 parts by mass, The aforementioned polycarbonate is blended in an amount of 13 to 48 parts by mass, The biomass material is blended in an amount of 10 to 45 parts by mass, The aforementioned dispersant is present in an amount of 0.75 to 1.5 parts by mass. Biomass resin composition.

[0048] [Item 2] The biomass resin composition described in item 1, The aforementioned bromine-based flame retardant is blended in an amount of 32 to 38 parts by mass, The hydrogenated styrene-based thermoplastic elastomer is blended in an amount of 6 to 10 parts by mass. Biomass resin composition.

[0049] [Item 3] The biomass resin composition described in item 1, The phosphazene-based flame retardant is blended in an amount of 7 to 15 parts by mass, The hydrogenated styrene-based thermoplastic elastomer is blended in an amount of 5 to 13 parts by mass. Biomass resin composition.

[0050] [Item 4] A molded article obtained by molding a biomass resin composition described in any one of items 1 to 3.

Claims

1. A biomass resin composition, A dispersant consisting of polycarbonate, a biomass material mainly composed of calcium carbonate, a hydrogenated styrene-based thermoplastic elastomer, and an acid-modified resin, and one of either a brominated flame retardant or a phosphazene-based flame retardant, However, it is included in the formula. When the entire biomass resin composition is 100 parts by mass, The aforementioned polycarbonate is blended in an amount of 13 to 48 parts by mass, The biomass material is blended in an amount of 10 to 45 parts by mass, The aforementioned dispersant is blended in an amount of 0.75 to 1.5 parts by mass. Biomass resin composition.

2. The biomass resin composition according to claim 1, The aforementioned bromine-based flame retardant is blended in an amount of 32 to 38 parts by mass, The hydrogenated styrene-based thermoplastic elastomer is blended in an amount of 6 to 10 parts by mass. Biomass resin composition.

3. The biomass resin composition according to claim 1, The phosphazene-based flame retardant is blended in an amount of 7 to 15 parts by mass, The hydrogenated styrene-based thermoplastic elastomer is blended in an amount of 5 to 13 parts by mass. Biomass resin composition.

4. A molded article obtained by molding a biomass resin composition according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Thermoplastic resin composition and molded article

    JP7288789B2